(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Maintainability has always been an elusive concept. Software maintainability is an external software quality attributes that estimate the complexity and effort required for maintaining software. The key concern of this review paper will be organized study on maintainability considering in view by its sub factors and metrics implementation of software maintainability keeping in mind to supports the maintenance process and facilitates the formation of improved quality software. In this paper studies accomplish a systematic literature review to have widespread facts of maintainability research and its feature factors and related measurements. Finally study does a comparative analysis on software maintainability models developed by various researchers/area experts including their contribution and limitation. In last our effort is to find the known wide-ranging and complete model or framework for quantifying the maintainability of object oriented software at an initial stage of development life cycle.